Karakteristik Kepemimpinan Pendidikan Sesuai dengan Ayat-ayat Al-Qur’an - Akhmad, Fandi; Sofia, Maulida Nurus; Jayanti, Gita Dwi; Lestari, Windi Mega; Wibawa, Zakki Teguh (MASALIQ, 2021)
Leadership is indispensable in education because a good, wise, fair, and responsible leader will make the educational institution he leads more advanced and can achieve goals in accordance with the wishes of all members. This writing aims to: 1) Understand the intellectuals about the foundation of good leadership and according to the guidance of the Qur'an. 2) Studying the character of leadership according to the guidance of the Qur'an Surah Al-Maidah:51-53. 3) Describe the accuracy of an educator in leading students listed in the Al-Qur'an Surah Al-Baqarah:247. 4) Explain the self-management of a leader based on Surah Shaad:26. 5) Explain the characteristics of leadership in accordance with Surah Al -Qalam:4, Al-Qashash:26, Al Imran:159, An-Nisa:58, and Surah Al-Furqan:74. The research method used is a descriptive approach and literature study. The results of writing: 1) In this case the leader must be able to unite and advance the diversity of Muslim life. 2) In the Quranic stories there is fertile land that can help the success of educators in carrying out their duties. 3) Good quality or quality in educational institutions must be built as early as possible which can be grown through the family environment. Reflecting a good attitude in a leader includes factors, one of which arises through religious norms.